2007
DOI: 10.1016/j.pain.2006.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent slowing of conduction velocity in uninjured L4 C fibers increases after an L5 spinal nerve injury in the rat

Abstract: Growing evidence suggests that uninjured afferents may play an important role in neuropathic pain following nerve injury. The excitability of nociceptive neurons in the L4 spinal nerve appears to be enhanced following an injury to the adjacent L5 spinal nerve. In this study, we investigated whether the action-potential conduction properties of unlesioned, unmyelinated fibers are also altered. A teased-fiber technique was used to record from single C fibers from the L4 spinal nerve of the rat in vitro. Repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…Differences in preparation (in vitro versus in vivo) or recording period for spontaneous activity (2 min [present study] versus 5 min [Wu et al, 2001]) may account for this discrepancy. Shim et al (2007) reported an enhancement of activity-dependent slowing of CV and supranormal CV in uninjured nerves following L5 SNL, providing further evidence that the excitability of uninjured primary afferent fibers can be altered in the presence of injured afferents. We did not analyze activity-dependent slowing of CVs in this study; however, given that the fibers appeared to be changing categories, we compared the distribution of CVs to provide some assurance that we were studying comparable Aδ-and C-fiber populations in the SNL and naïve groups.…”
Section: Physiological Correlates To Behavioral Changesmentioning
confidence: 66%
“…Differences in preparation (in vitro versus in vivo) or recording period for spontaneous activity (2 min [present study] versus 5 min [Wu et al, 2001]) may account for this discrepancy. Shim et al (2007) reported an enhancement of activity-dependent slowing of CV and supranormal CV in uninjured nerves following L5 SNL, providing further evidence that the excitability of uninjured primary afferent fibers can be altered in the presence of injured afferents. We did not analyze activity-dependent slowing of CVs in this study; however, given that the fibers appeared to be changing categories, we compared the distribution of CVs to provide some assurance that we were studying comparable Aδ-and C-fiber populations in the SNL and naïve groups.…”
Section: Physiological Correlates To Behavioral Changesmentioning
confidence: 66%
“…Published studies in mice have described pain behavior after ligation of the L5 spinal nerve, with [8,30] or without [20,22,28,33] ligation of the L6 nerve. Our finding of only a minor contribution of the mouse L5 spinal nerve to the sciatic nerve predicts that L5 ligation will minimally affect the population of afferents going to the foot or sciatic nerve in the thigh.…”
Section: Consideration Of the Published Literature In The Context Of mentioning
confidence: 99%
“…In a case of neuropathic pain, it is presumed that a nerve injury leads to persistent alterations in the properties of adjacent uninjured, unmyelinated fibers because of changes in expression of ion channels responsible for the membrane excitability (Gold et al, 2003;Shim et al, 2007). In the effort to develop effective treatments for atypical orofacial pain, it is important to establish an appropriate model, and to investigate the exact mechanisms of ectopic heat hyperalgesia induced by local inflammation in the orofacial region.…”
Section: Introductionmentioning
confidence: 99%